Trends in Digital Based Physics Teaching Material Development and Their Impact on Twenty First Century Learning: A Systematic Literature Review - Alexander Mahombar; Putut Marwoto; Sutikno; Masturi; Bambang Subali (Universitas Negeri Padang, 2026)
The rapid advancement of digital technology has transformed physics learning into a more interactive and student-centered process that supports twenty first century competencies. However, studies on digital-based physics teaching materials remain fragmented and have not comprehensively explored publication trends, teaching material types, research methods, research networks, and their impacts on twenty first century learning. Therefore, this research purpose to analyze and visualize trends in the development of digital-based physics teaching materials from 2020 to 2025. This research employed a Systematic Literature Review (SLR) combined with bibliometric analysis using Bibliometrix and VOSviewer software. The data consisted of 34 Scopus-indexed articles selected through the PRISMA procedure based on relevance and publication quality. The findings indicate that research publications on digital-based physics teaching materials increased significantly during the analyzed period, with e-modules emerging as the most dominant type of teaching material. The research also revealed that digital teaching materials positively contribute to improving students’ conceptual understanding, critical thinking, higher-order thinking skills, scientific literacy, creativity, collaboration, and learning independence. In conclusion, digital-based physics teaching materials have become strategic learning innovations that support adaptive and technology-integrated physics education in the twenty first century and provide important references for future educational development.